What Could You Really Learn on Your Own?: Understanding the Epistemic Limitations of Knowledge Acquisition. Issue 2 (11th December 2015) - Lockhart, Kristi L.; Goddu, Mariel K.; Smith, Eric D.; Keil, Frank C.
Abstract : Three studies explored the abilities of 205 children (5–11 years) and 74 adults (18–72 years) to distinguish directly versus indirectly acquired information in a scenario where an individual grew up in isolation from human culture. Directly acquired information is knowledge acquired through firsthand experience. Indirectly acquired information is knowledge that requires input from others. All children distinguished directly from indirectly acquired knowledge (Studies 1–3), even when the indirectly acquired knowledge was highly familiar (Study 2). All children also distinguished difficult‐to‐acquire direct knowledge from simple‐to‐acquire direct knowledge (Study 3). The major developmental change was the increasing ability to completely rule out indirect knowledge as possible for an isolated individual to acquire.